Pemetaan Struktur Intelektual Penelitian Akuntansi Organisasi Nirlaba: Analisis Bibliometrik dalam Perspektif ISAK 35 - Savirna Ulfa Cahyani Putri; Dilla Diniya; Riten Sumarni; Nabil FR; Aditya Saputra; Abdillah Ishak (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The enactment of ISAK 35 as a financial reporting standard for non-profit entities has increased attention toward transparency, accountability, and reporting quality in nonprofit organizations. This study aims to map the intellectual structure, publication trends, and thematic development in nonprofit accounting research from the perspective of ISAK 35 using a bibliometric approach. The research employs a quantitative descriptive method based on Scopus data, analyzed using VOSviewer. Following PRISMA-based literature screening, 170 articles were identified for analysis. Results demonstrate that the most dominant topics are ISAK 35 implementation, nonprofit financial reporting, and accountability and transparency. Keyword network analysis reveals that 'nonprofit organization' serves as the central node connecting clusters including organizational governance, stakeholders, decision-making, funding, philanthropy, innovation, and sustainable development. Trend analysis indicates a research focus shift from traditional themes such as civil society and voluntary approaches toward contemporary issues including innovation, sustainability, social entrepreneurship, and accounting system digitalization. These findings confirm that nonprofit accounting research continues to evolve dynamically and multidisciplinarily with growing emphasis on sustainability, digital transformation, and accountability. This study is expected to contribute to nonprofit accounting literature and guide researchers, practitioners, and regulators in directing future research and policy development related to ISAK 35 implementation in Indonesia.